Gender transformative intervention profile 2: Addressing normative constraints to building women’s economic resilience in the cassava agrifood system in Tanzania - Mwakanyamale, Devis; Msita, Sarah; Shumbusho, E.; Mushema, G.; Kagya, A.; Asimwe, I. (CGIAR System Organization, 2024)
Profile 2